ANALISIS PERBANDINGAN KINERJA ALGORITMA FIXED LENGTH BINARY ENCODING DAN ALGORITMA ELIAS GAMMA CODE DALAM KOMPRESI FILE TEKS - Pratiwi, Dian; Zebua, Taronisokhi (STMIK Budi Darma, 2019)
Now days, there are many algorithms developed for data compression, but there is no one that is good for compressing various types of files because of different characteristics or file structures. This research explained the result of two compression algorithms in order to know the performance comparison between the Fixed Length Binary Encoding (FLBE) algorithm and the elias gamma code algorithm in compressing text files, especially in format rtf. The parameters being compared are the ratio of compression, compression ratio, redundancy and time. Based on the test results show that the fixed length binary encoding algorithm is better than the elias gamma code algorithm where the average ratio of compression results of fixed length binary encoding algorithm is 1.66 bits while the elias gamma code is 1.62 bits. The average compression ratio of fixed length binary encoding algorithm is 60.9% while Elias Gamma Code is 62.20%. The average value of the redundancy of the fixed length binary encoding algorithm is 39.1% while the gamma code elias is 37.79%. The average time compression value of the fixed length binary encoding algorithm is 16 ms while the elias gamma code is 21 ms.Keywords: comparison, compression, FLBE algorithm, Elias Gamma Code Algorithm, text, rtf